Earnings of students who leave post-16 education with A level grades which have “little currency” - Gill, Tim (International Journal of Population Data Science, 2025)
Objectives The main aim of this research was to investigate what happens to students who leave school/college with A-level grades which have ‘little currency’ (i.e., grades D or below). Are their labour market returns (earnings) different from those of students with better grades (grades C or above)? Method We used Longitudinal Education Outcomes data, which connects individuals’ education with their employment and earnings. We selected students who left school between 2004/05 and 2011/12 and recorded their earnings in each year until 2019/20. We focused on A-level students who achieved: ‘E grades only’ or ‘D or E grades only’. Outcomes for students in these groups were compared to those of other groups: students with A-levels all at grades C or above; students with BTECs. Descriptive statistics on earnings, overall and by students’ characteristics were produced. We also carried out multilevel regression analyses to control for individual-level characteristics and cohort. Results In the first few years after leaving school, the students with low A level grades (best grade E or best grade D) had very slightly higher mean daily earnings than students in the other groups. However, from year 5 onwards, students with better grades (lowest grade C) had a higher mean, and this advantage increased over time. There were some differences in this result between students of different ethnic groups or gender. In particular, from year 5 onwards, Asian, Black, and Chinese students had more of an advantage (than White students did) if they were in the ‘lowest grade C’ group compared with the other groups. Conclusion The outcomes of this work provide evidence for policy decision-making which may benefit young people in England. Students who finish school with low A level grades should not be forgotten. Knowing their outcomes will help understand whether policy changes/interventions are needed to improve their prospects.